REFORMA A LEY Y REGLAMENTO DE SERVICIO PÚBLICO INCORPORANDO AL INFORME PREVIO AL SUMARIO ADMINISTRATIVO LA OBLIGACIÓN DE NOTIFICARLO AL AFECTADO EN ARMONIA CON LA CONSTITUCIÓN - Reyes Barahona, Santiago David (2015)
This research topic is what made on the problems that exist in the administrative law branch, specifically in the field of public sector concerning sanctions that may be imposed to the public employee, through administrative proceedings, in which the actions pre-start, it is now violated the right to defense, which seriously affects the public server. For the development of this thesis I set as a general objective to analyze the regulations applicable to the conduct of the administrative investigation procedure in relation to the effective implementation of the constitutional provisions regarding the fulfillment of guarantees of due process, which was established thanks the application of methods and scientific techniques that guided me to achieve results that allowed me to support the proposal to amend the Act and Regulations Public Service. More than bibliographic doctrinaire collection, thirty surveys and three interviews with lawyers in our city, the same as they were encamidas to determine the violation of rights of public employees in the conduct of administrative proceedings, causing irreparable damage to be made the interests of the employee. The reform planted the Act and Regulations Public Service is designed so that all public servants who are subject to disciplinary regime, have a real and effective legal protection without involvement of any kind.